A natural agonist of mosquito TRPA1 from the medicinal plant Cinnamosma fragrans that is toxic, antifeedant, and repellent to the yellow fever mosquito Aedes aegypti - Inocente, Edna Alfaro; Shaya, Marguerite; Acosta, Nuris; Rakotondraibe, L. Harinantenaina; Piermarini, Peter M. (PLOS Neglected Tropical Diseases, 2018)
Author summary New insecticides and repellents are urgently needed to improve the control of mosquito vectors of emerging diseases, such as Zika. Here we discover that the bark of a Madagascan medicinal plant (Cinnamosma fragrans) is enriched with a molecule (cinnamodial) that is toxic, antifeedant, and repellent to the principal mosquito vector of Zika virus (Aedes aegypti). We also show that the mechanism behind some of cinnamodial’s activity in mosquitoes is associated with its ability to activate a receptor (TRPA1) that mosquitoes use to detect heat and noxious chemicals in their environment. The results from our work may lead to the development of new insecticides and chemicals that can be used to control mosquito vectors.